The epic guide to Dragon Masters - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters., 2024)
"This is the official Dragon Masters guidebook. These pages are filled with facts about Dragon Masters and their powerful dragons. You will learn the history of the Dragon Masters, read about wizards from around the world, and be able to study castle and land maps. You'll even find top secret notes from Griffith, the royal wizard of Bracken!"--Back cover.